miRNA gene counts in chromosomes vary widely in a species and biogenesis of miRNA largely depends on transcription or post-transcriptional processing of coding genes - Ghorai, Atanu; Ghosh, Utpal (Frontiers in Genetics, 2014)
MicroRNAs target specific mRNA(s) to silence its expression and thereby regulate various cellular processes. We have investigated miRNA gene counts in chromosomes for 20 different species and observed wide variation. Certain chromosomes have extremely high number of miRNA gene compared with others in all the species. For example, high number of miRNA gene in X chromosome and the least or absence of miRNA gene in Y chromosome was observed in all species. To search the criteria governing such variation of miRNA gene counts in chromosomes, we have selected three parameters- length, number of non-coding and coding genes in a chromosome. We have calculated Pearson’s correlation coefficient of miRNA gene counts with length, number of non-coding and coding genes in a chromosome for all 20 species. Major number of species showed that number of miRNA gene was not correlated with chromosome length. 85% of species under study showed strong positive correlation coefficient (r≥0.5) between the numbers of miRNA gene vs non-coding gene in chromosomes as expected because miRNA is a sub-set of non-coding genes. 55% species under study showed strong positive correlation coefficient (r≥0.5) between numbers of miRNA gene vs coding gene. We hypothesize biogenesis of miRNA largely depends on coding genes, an evolutionary conserved process. Chromosomes having higher number of miRNA genes will be most likely playing regulatory roles in several cellular processes including different disorders. In humans, cancer and cardiovascular disease associated miRNAs are mostly intergenic and located in Chromosome 19, X, 14 and 1.